Hepatitis C reinfection by treatment pathway among people who inject drugs in Tayside, Scotland. Issue 12 (6th October 2021) - Caven, Madeleine; Baiano, Cassandra X.; Robinson, Emma M.; Stephens, Brian; Macpherson, Iain; Dillon, John F.
Abstract: The efficacy of direct‐acting antivirals (DAA) provides an excellent opportunity to scale up HCV diagnosis and treatment, achieving the WHO target of HCV elimination by 2030. However, HCV reinfection among people who inject drugs (PWID) remains a concern and may impede elimination efforts. We assessed reinfection rates among PWID across six specialized treatment pathways, following DAA‐based and interferon‐based therapies in Tayside, Scotland. Data were collected retrospectively for every treatment episode that resulted in a sustained viral response (SVR) after undergoing treatment. Reinfection rates were calculated for each treatment pathway: hospital outpatient clinic; community pharmacy; drug treatment outreach; prison clinic; nurse‐led outreach clinic; and injection equipment provision site. Reinfection is defined as a positive RNA test result after SVR. Incidences of reinfection are expressed in 100 person‐years (PYs). In total, 916 treatment episodes met selection criteria. Of these, 100 reinfections were identified, generating an overall reinfection rate of 5.27 per 100 PYs (95%CI: 4.36–6.38). The hospital outpatient clinic had the lowest reinfection incidence (1.81 per 100 PYs, 95%CI: 1.11–2.93), with the injection equipment provision site treatment pathway having the highest reinfection incidence (19.89 per 100 PYs, 95%CI: 14.91–26.54). The incidence of reinfection among those treated with interferon‐based therapies and those treated with DAA‐based therapies was 4.93 per 100 PYs (95%CI: 3.97–6.11) and 7.17 per 100 PYs (95%CI: 4.75–10.82), respectively. Specialized treatment pathways in Tayside yield varying reinfection incidence rates, with different subpopulations of patients at varying risk of reinfection post‐SVR. Results suggest that resources should be targeted at the injection equipment provision site pathway in order to reduce the incidence of reinfection and achieve elimination targets. The study found comparable rates of reinfection following interferon‐based and DAA‐based therapies, providing support for widening access to treatment services.